2024
DOI: 10.20944/preprints202405.1743.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Parental Mental Health, Gender, and Lifestyle Effects on Post-Pandemic Child and Adolescent Psychosocial Problems: A Cross-Sectional Survey in Northern Italy

Verena Barbieri,
Giuliano Piccoliori,
Adolf Engl
et al.

Abstract: Background: The exacerbation of psychosocial problems among children and adolescents during the coronavirus disease 2019 (COVID-19) pandemic necessitates an assessment of the long-term mental health impact of pandemic interventions. Focusing on both pandemic-related factors and demographic variables, such as gender and daily habits, an analysis was conducted to under-stand how these elements continue to affect young populations in the post-pandemic era. Methods: In April 2023, a comprehensive online survey was… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 39 publications
0
0
0
Order By: Relevance
“…The COVID-19 pandemic has left a lasting mark on the mental health of youth in South Tyrol, particularly among adolescents. Two prominent challenges that emerged during and after the pandemic—persistent mental health problems and vaccine hesitancy—illustrate the need for change [ 4 , 8 , 11 ]. While the immediate crisis highlighted low vaccine uptake and the need for acute psychosocial support for youth, it also revealed gaps in health literacy and preventive measures.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The COVID-19 pandemic has left a lasting mark on the mental health of youth in South Tyrol, particularly among adolescents. Two prominent challenges that emerged during and after the pandemic—persistent mental health problems and vaccine hesitancy—illustrate the need for change [ 4 , 8 , 11 ]. While the immediate crisis highlighted low vaccine uptake and the need for acute psychosocial support for youth, it also revealed gaps in health literacy and preventive measures.…”
Section: Resultsmentioning
confidence: 99%
“…During the COVID-19 pandemic, South Tyrol, like other parts of the world, experienced an increase in mental health challenges, particularly among adolescents. Barbieri et al [ 11 ] highlighted the persistence of high levels of psychosocial problems among children and adolescents in the region. This study showed that the psychological impact of the pandemic may have long-lasting effects on young people’s mental well-being.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations